Hubungan Kemampuan Pemecahan Masalah Terhadap Kualitas Relationship Pranikah Pada Mahasiswa Universitas Muhammadiyah Surakarta - Deko Bagus Wahyu Handoko; Anisa Az Zahra; Muhammad Daffa Luthfi Bahtiar; Salsabilla Arifatul Husna (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Problem-solving ability is a crucial cognitive skill in daily life, including in interpersonal relationships. The quality of premarital relationships is influenced by various factors, one of which is problem-solving ability. However, the relationship between these two variables remains unclear. This study used a quantitative survey design with a sample of 92 students from Universitas Muhammadiyah Surakarta who were in premarital relationships, selected using the Simple Random Sampling technique. Data were collected through a Likert-scale questionnaire, using the Independent-Interdependent Problem-Solving Scale (IIPSS) to measure problem-solving ability and the Relationship Assessment Scale (RAS) to assess the quality of premarital relationships. Data analysis was conducted using the Spearman Rho correlation test and linear regression analysis. The analysis showed no significant relationship between problem-solving ability and the quality of premarital relationships (ρ = 0.042; p = 0.694). The R² value of 0.001 indicates that problem-solving ability explains only 0.1% of the variability in relationship quality, suggesting that other factors play a more dominant role. These findings suggest that other factors, such as emotional regulation and interpersonal communication, may have a greater influence on relationship quality than problem-solving ability. The limitations of this study include the low variability of problem-solving scores and the lack of consideration for additional influencing factors. Future research is recommended to include mediating variables such as emotional regulation and interpersonal communication to gain a more comprehensive understanding.